Peculiarities of interaction between market participants in the context of its globalization - Pavlov, Kostiantyn; Sadovska, Margaryta; Marchuk, Vadym; Osvitsynsky, Bohdan (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article examines the peculiarities of interaction between market participants in the context of globalization. The key factors affecting the market system, such as monopolization, government intervention, financial speculation, and environmental restrictions, are analyzed. The author discusses the consequences of globalization for countries with different levels of economic development and suggests methods of solving problems related to the violation of market mechanisms. In particular, antitrust policy, international cooperation, and environmental regulation are considered. While globalization has created new opportunities for economic development, it has also brought significant challenges that require effective measures to maintain the stability and competitiveness of market relations. To ensure the effectiveness of the market mechanism, it is necessary to implement comprehensive reforms to strengthen antitrust regulation, control financial markets, develop the digital economy, and ensure environmental sustainability.

У статті розглядаються особливості взаємодії учасників ринку в умовах глобалізації. Аналізуються ключові чинники, що впливають на роботу ринкової системи, такі як монополізація, державне втручання, фінансові спекуляції та екологічні обмеження. Обговорюються наслідки глобалізації для країн з різними рівнями економічного розвитку та пропонуються методи вирішення проблем, пов'язаних із порушенням ринкових механізмів. Зокрема, розглядаються антимонопольна політика, міжнародне співробітництво та екологічне регулювання. Хоча глобалізація створила нові можливості для розвитку економіки, вона також принесла значні виклики, які потребують ефективних заходів для підтримки стабільності та конкурентоспроможності ринкових відносин. Для забезпечення ефективності ринкового механізму необхідно впроваджувати комплексні реформи, спрямовані на посилення антимонопольного регулювання, контроль за фінансовими ринками, розвиток цифрової економіки та забезпечення екологічної стійкості
Особливості взаємодії суб'єктів ринку за умов його глобалізації
Keywords: globalization; market mechanism; monopolization; financial speculation; digital markets; antitrust policy; глобалізація; ринкові механізми; екологічні обмеження; фінансові спекуляції; цифрові ринки; антимонопольна політика